POTENSI KARBON AKTIF KULIT NANAS (Ananas comosus) SEBAGAI ADSORBEN LOGAM BERAT Pb DENGAN PERBANDINGAN AKTIVATOR NaOH DAN HCl - Rusli, Rusli; Fatimah, Siti; Gusti, Herdi Idriawien; Jumrah, Elfira (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2025)
The increasing need for activated carbon with biological raw materials in Indonesia is very rapid, supported by technological and industrial advances. Activated carbon is quite important in the industrial world which is used as an adsorbent. This research uses pineapple skin as a raw material for making activated carbon. The purpose of this study was to determine the potential and adsorption capacity of activated carbon from pineapple peels. Activated carbon is prepared by carbonating pineapple skin at 600oC for 5 minutes and then activated with HCl and NaOH activators by soaking for 24 hours. Furthermore, the absorption of Pb was tested using AAS to determine the absorption potential of pineapple peel activated carbon for heavy metalsThe test results showed that activated carbon using HCl had a yield of 9.2%, moisture content of 12.68%, and ash content of 35.88%. Meanwhile, activated carbon using NaOH had a yield of 9.5%, moisture content of 32.38%, and ash content of 21.03%. The adsorption capacities were 0.0045 mg/g (HCl) and 0.0053 mg/g (NaOH). These results indicate that pineapple peel has strong potential as a raw material for activated carbon in heavy metal adsorption, in accordance with SNI 06-3730-1995.